PENGARUH BERBAGAI VARIABEL INDIVIDU TERHADAP PERILAKU KARYAWAN DALAM ORGANISASI - Andi Widiawati (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
The problem of the behavior of individuals and groups is a very complicated problem often faced by all managers of various organizations, therefore it is essential to be studied and understood so that organizational goals can be achieved effectively and efficiently. Organizational leaders pay more attention to various variables individuals within the organization, it is very influential on behavior caused by the employees in the organization in support of the achievement of organizational goals. Results of research on the relationship between satisfaction and -produktivitas have happy employees create goals based on the assumption that it will get the highest happiness high productivity turns out wrong , the leaders will produce better things by directing their attention mainly keapa that will help employees be more productive .